Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Drivers of seasonal and decadal change on an estuarine beach in a fetch-limited temperate embayment - David M. Kennedy; R. Jak McCarroll; Thomas E. Fellowes; Shari L. Gallop; Nicolas Pucino; Sarah L. McSweeney; Ana Vila-Concejo; Ruth Reef; Runjie Yuan; Rafael Carvalho; Tran Huy Quang; Daniel Ierodiaconou (Marine Geology, 2023)

Unsteady Linearisation of Bed Shear Stress for Idealised Storm Surge Modelling - Pieter C. Roos; Giordano Lipari; Chris Pitzalis; Koen R. G. Reef; Gerhardus H. P. Campmans; Suzanne J. M. H. Hulscher (Journal of Marine Science and Engineering, 2021)
The modelling of time-varying shallow flows, such as tides and storm surges, is complicated by the nonlinear dependency of bed shear stress on flow speed. For tidal flows, Lorentz’s linearisation circumvents nonlinearity by specifying a (steady) friction coefficient r based on a tide-averaged criterion of energy equivalence. However, this approach is not suitable for phenomena with episodic and irregular forcings such as storm surges. Here, we studied the implications of applying Lorentz’s energy criterion in an instantaneous sense, so that an unsteady friction coefficient r(t) adjusts to the temporal development of natural wind-driven flows. This new bed-stress parametrisation was implemented in an idealised model of a single channel, forced by time-varying signals of wind stress (acting over the entire domain) and surface elevation (at the channel mouth). The solution method combines analytical solutions of the cross-sectionally averaged linearised shallow-water equations, obtained in the frequency domain, with an iterative procedure to determine r(t). Model results, compared with a reference finite-difference solution retaining the quadratic bed shear stress, show that this new approach accurately captures the qualitative and quantitative aspects of the surge dynamics (height and timing of surge peaks, sloshing, friction-induced tide-surge interaction) for both synthetic and realistic wind forcings.

The Impact of Storm-Induced Breaches on Barrier Coast Systems Subject to Climate Change—A Stochastic Modelling Study - Koen R. G. Reef; Pieter C. Roos; Tessa E. Andringa; Ali Dastgheib; Suzanne J. M. H. Hulscher (Journal of Marine Science and Engineering, 2020)
Storms can have devastating impacts on barrier coasts causing coastal erosion, partial inundation, and possibly the breaching of barrier islands. The breaching of barrier islands provides a mechanism for the creation of new tidal inlets that connect the backbarrier basin (or lagoon) and the outer sea. As a new tidal inlet affects both the basin and the hydrodynamics of existing inlets, it is important to understand why an initial breach either closes or may evolve into a new tidal inlet. To this end, we performed a Monte Carlo analysis using an idealized model capable of simulating the long-term morphological evolution of multiple tidal inlets connected to a single backbarrier basin. To do so required the creation of a stochastic shell, as a new element around this existing barrier coast model. Our results demonstrate that barrier coast systems tend towards an equilibrium value for the number of inlets per kilometer of barrier coast and total inlet cross section. This even holds with the continuous stochastic forcing of storm-induced breaches. This finding implies that if a new breach opens in a coast that is already in equilibrium, existing inlets will shrink and may close if the new breach remains open. Furthermore, we find that climate-driven changes in storm frequency will modify the timescales in which barrier coasts reach their equilibrium state. Finally, we find that the distance between a new breach and its nearest neighbor is more important for its survival than the size of the breach or the degree of saturation of the barrier coast.

Carbon and Nitrogen Sequestration of Melaleuca Floodplain Wetlands in Tropical Australia - M. F. Adame; R. Reef; V. N. L. Wong; S. R. Balcombe; M. P. Turschwell; E. Kavehei; D. C. Rodríguez; J. J. Kelleway; P. Masque; M. Ronan (Ecosystems, 2020)

Time-varying storm surges on Lorentz’s Wadden Sea networks - Koen R. G. Reef; Giordano Lipari; Pieter C. Roos; Suzanne J. M. H. Hulscher (Ocean Dynamics, 2018)

The effects of elevated CO 2 and eutrophication on surface elevation gain in a European salt marsh - Ruth Reef; Tom Spencer; Iris Mӧller; Catherine E. Lovelock; Elizabeth K. Christie; Anna L. McIvor; Ben R. Evans; James A. Tempest (Global Change Biology, 2017)
Salt marshes can play a vital role in mitigating the effects of global environmental change by dissipating incident storm wave energy and, through accretion, tracking increasing water depths consequent upon sea level rise. Atmospheric CO 2 concentrations and nutrient availability are two key variables that can affect the biological processes that contribute to marsh surface elevation gain. We measured the effects of CO 2 concentrations and nutrient availability on surface elevation change in intact mixed‐species blocks of UK salt marsh using six open‐top chambers receiving CO 2 ‐enriched (800 ppm) or ambient (400 ppm) air. We found more rapid surface elevation gain in elevated CO 2 conditions: an average increase of 3.4 mm over the growing season relative to ambient CO 2 . Boosted regression analysis to determine the relative influence of different parameters on elevation change identified that a 10% reduction in microbial activity in elevated CO 2 ‐grown blocks had a positive influence on elevation. The biomass of Puccinellia maritima also had a positive influence on elevation, while other salt marsh species (e.g. Suaeda maritima ) had no influence or a negative impact on elevation. Reduced rates of water use by the vegetation in the high CO 2 treatment could be contributing to elevation gain, either directly through reduced soil shrinkage or indirectly by decreasing microbial respiration rates due to lower redox levels in the soil. Eutrophication did not influence elevation change in either CO 2 treatment despite doubling aboveground biomass. The role of belowground processes (transpiration, root growth and decomposition) in the vertical adjustment of European salt marshes, which are primarily minerogenic in composition, could increase as atmospheric CO 2 concentrations rise and should be considered in future wetland models for the region. Elevated CO 2 conditions could enhance resilience in vulnerable systems such as those with low mineral sediment supply or where migration upwards within the tidal frame is constrained.